Pengaruh Bakat dalam Pencapaian Akademik Mahasiswa UNAI - Albinur Limbong (Fakultas Teknologi Informasi - Universitas Advent Indonesia, 2019)
This paper is a report of a study about the influence of talent on the academic achievement of UNAI student batch 2016. The new students accepted in 2016 had to do talent test conducted by a professional institution giving three options of results namely Recommended, Doubted, Not Recommended. The academic achievement is seen in two parameters, i.e. the degree of graduation and GPA, observed for 6 semesters (three academic years) starting from 2016/2017 until 2018/2019. The study shows that the degree of graduation for UNAI student batch 2016 is 82%, or the degree of drop out is 18%. The highest degree of graduation is achieved by the students of the faculty of teacher training and education, i.e. 94.4%, while the lowest figure is achieved by the students of faculty of philosophy, i.e. 75%. In terms of academic achievement (GPA), there is a slight improvement of GPA from year to year. However, there is siginificant difference in the academic achievement between students considered as talented, less talented and not talented. The fact that there is siginifanct influence of talent onto the achievement of UNAI, then it is very important to study some other possible faktors namely motivation, IQ, and other external factors.